Mindfulness-based online intervention on mental health among undergraduate nursing students during coronavirus disease 2019 pandemic in Beijing, China: A randomized controlled trial - Dai, Zhenwei; Jing, Shu; Wang, Hao; Xiao, Weijun; Huang, Yiman; Chen, Xu; Fu, Jiaqi; Pan, Chen; Tang, Qiuping; Wang, Huan; Su, Xiaoyou (Frontiers in Psychiatry, 2022)
Objective To evaluate the effect of mindfulness intervention on improving mental health among undergraduate nursing students during the coronavirus disease 2019 (COVID-19) pandemic in China. Methods An online mindfulness intervention course named Mindfulness Living With Challenge (MLWC) was developed by the research team, and a randomized controlled trial using MLWC among Chinese undergraduate nursing students was carried out. A total of 120 undergraduate nursing students were randomized into control (60 students) and intervention groups (60 students) via a WeChat mini program. Self-administered questionnaire surveys were conducted at pre- and post-intervention, measuring depression, anxiety, stress, mindfulness, and perceived social support. After intervention, the acceptance of the online mindfulness course among participants was assessed by employing the theory of technology acceptance model (TAM). Results Among the enrolled 120 participants, 86.67% (52/60) and 93.33% (56/60) of the intervention and control groups remained completed the trial and the questionnaire surveys. Compared with the control group, the reduction of anxiety and stress symptoms, as well as the improvement of mindfulness level and perceived social support in the MLWC intervention group were statistically significant (P < 0.05), while the change in depression was not statistically significant. The scores of the four dimensions in TAM ranged from (5.88 ± 0.94) to (5.91 ± 0.97). Conclusion Online mindfulness intervention implemented in this study is effective in improving mental health among undergraduate nursing students, and they were interested in this intervention. Clinical trial registration [www.ClinicalTrials.gov], identifier [ChiCTR2 200058103].